Measuring knowledge exploration and exploitation in universities and the relationship with global ranking indicators - Marta Peris-Ortiz; Dayanis García-Hurtado; Alberto Prado Román (European Research on Management and Business Economics (ERMBE), 2023)
This study examines the primary external control mechanism of universities (i.e. international rankings) to assess their knowledge exploration and exploitation performance. A taxonomy of indicators from the perspective of ambidexterity is presented. The most prestigious global university rankings are assessed within this theoretical framework. Exploration and exploitation indicators in the rankings are analysed in relation to the input, output and outcomes of universities. The results indicate a predominance of exploitation indicators in rankings. The potential managerial implications of this imbalance in indicators are discussed.
Keywords: O31; O32; 650; Knowledge exploration; Knowledge exploitation; University rankings